Body Disownership in Complex Posttraumatic Stress Disorder - Ataria, Yochai (Palgrave Macmillan US, 2018)
This book explores the long-term outcomes of severe and ongoing trauma-particularly complex posttraumatic stress disorder (C-PTSD)-from phenomenological and cognitive perspectives. For example, C-PTSD can result in impairments at the body-schema level. In order to survive, trauma victims may conduct their lives at the body-image level, thus producing a mismatch between body schema and body image. In turn, as in the case of somatoparaphrenia and body integrity identity disorder, this incongruity can result in body disownership, which will affect long-term outcomes of severe and ongoing trauma.